Long-term disease-free survival of an undifferentiated pleomorphic sarcoma of the spleen: A case report and literature review. Issue 47 (25th November 2022) - Tomioka, Atsushi; Asakuma, Mitsuhiro; Kawaguchi, Nao; Komeda, Koji; Shimizu, Tetsunosuke; Uchiyama, Kazuhisa; Lee, Sang-Woong
Abstract : Introduction: Undifferentiated pleomorphic sarcoma (UPS) primarily occurs in the soft tissues of the extremities, trunk, and retroperitoneum. As the primary UPS of the spleen (splenic UPS) is extremely rare, to the best of our knowledge, only 19 cases have been reported in English literature. No cases of long-term survival without a local or distant recurrence have been reported. Patient concerns: We report the case of a 37-year-old man who was referred to our hospital for a splenic tumor. He had no past medical or relevant familial history. On abdominal computed tomography (CT), a low attenuation solid mass and cystic component with mural calcifications were present at the lower pole of his spleen. The fluorodeoxyglucose-positron emission tomography (CT) indicated it as malignant tumor of the spleen. Diagnoses: The patient's provisional diagnosis was deduced to be angiosarcoma, which was the most common malignant tumor of the spleen. Interventions: An elective laparoscopic splenectomy was performed, and the histology of the tumor was consistent with UPS (pT1, pN0, cM0, and AJCC 8th ). No adjuvant therapy was administered. Outcomes: Ten years have passed since the patient's splenectomy, and he continues to do well, without evidence of local or distant recurrence. Lessons: To the best of our knowledge, this is the first case of long-term recurrence-free survival after surgical management of a splenic UPS. It is probable that radical splenectomy during the disease played the most important role in the patient's long-term survival. Understanding the characteristic findings of a splenic UPS in an abdominal CT may help to diagnose properly.